ASSESSMENT OF LOCAL HEALTH SYSTEM’S RESPONSIVENESS TO TUBERCULOSIS IN SELECT MUNICIPALITIES IN PHILIPPINES - Nieva Jr, Romulo F (LIFE: International Journal of Health and Life-Sciences, 2017)
Tuberculosis (TB) remains one of the leading causes of morbidity and mortality in Philippines. The structure of the TB control delivery system in the Philippines is devolved that has led to some significant gaps in responding to the health needs of the population across the country. The study was carried out to assess how municipalities implement TB programs using the local health systems model; and to document existing policies and initiatives in the local government units. It also applied a desk review of existing practices in 20 municipalities, plus key informant interviews with 15 mayors, 20 municipal health officers and 15 TB coordinators. Findings indicated that less than a quarter of municipalities had investment plan for health on TB and 41% had local policy supporting TB program. Additionally, 25% had specifically allocated budget for TB, 82% had their facilities accredited by PhilHealth, and 59% had inadequate number of health workers for TB program. About 18% had x-ray facilities, and 41% had enough supply and buffer of medicines. Eighteen per cent (18%) had actively engaged private and government hospitals for TB program, and 100% did not screen TB patients for HIV. Data showed the gaps in the municipal health systems to address TB issues. Thus, local leaders must be capacitated and supported by stakeholders to strengthen service delivery for TB. This underscores the big role of local leadership in TB prevention and control program being the frontline policy maker and service provider.